Rancang Bangun Sistem Monitoring Ruang Kelas Berbasis Internet of Things pada Universitas Pamulang - Joko Riyanto; Farida Nurlaila; Heri Haerudin; Bayu Tirto Jarastino (Jurnal Informatika Universitas Pamulang, 2020)
In a classroom, ideally there are facilities such as chairs, desks, blackboards, and electronic devices used such as air conditioners (AC), lamps and projectors. However, in its use, there are actions that are not responsible for maintaining the facility so that it causes losses. An internet of things-based classroom monitoring system is needed to solve existing problems. This system has the ability to remotely operate electronic facilities in classrooms such as air conditioning, electricity and lights, monitor access to classrooms, process data, print activity monitoring reports, to monitor the current conditions of a room. This system consists of three parts, namely the database part, the microcontroller section and the software section. The database section contains data on access cards or fingerprints, room usage schedules, room temperature and humidity. The methodology for designing and building a classroom monitoring system uses the waterfall methodology. In this methodology, several steps are taken to build a system, namely: system requirements analysis, hardware design and software engineering, system design, system implementation, system testing, and system maintenance. Based on the test results, this system can record input data on the microcontroller section and display it in the software section for real-time monitoring and controlling of classrooms and minimizing damage to existing facilities in the classroom. Monitoring of classroom use that is not according to the schedule of use can be carried out and controlled remotely in real-time.